Application of a hand-held laser methane detector for measuring enteric methane emissions from cattle in intensive farming - Kang, Kyewon; Cho, Hyunjin; Jeong, Sinyong; Jeon, Seoyoung; Lee, Mingyung; Lee, Seul; Baek, Yulchang; Oh, Joonpyo; Seo, Seongwon (Journal of animal science, 2022)
Abstract The hand-held laser methane detector (LMD) technique has been suggested as an alternative method for measuring methane (CH4) emissions from enteric fermentation of ruminants in the field. This study aimed to establish a standard procedure for using LMD to assess CH4 production in cattle and evaluate the efficacy of the protocol to detect differences in CH4 emissions from cattle fed with diets of different forage-to-concentrate (FC) ratios. Experiment 1 was conducted with four Hanwoo steers (584 ± 57.4 kg body weight [BW]) individually housed in metabolic cages. The LMD was installed on a tripod aimed at the animal’s nostril, and the CH4 concentration in the exhaled gas was measured for 6 min every hour for 2 consecutive days. For the data processing, the CH4 concentration peaks were identified by the automatic multi-scale peak detection algorithm. The peaks were then separated into those from respiration and eructation by fitting combinations of two of the four distribution functions (normal, log-normal, gamma, and Weibull) using the mixdist R package. In addition, the most appropriate time and number of consecutive measurements to represent the daily average CH4 concentration were determined. In experiment 2, 30 Hanwoo growing steers (343 ± 24.6 kg BW), blocked by BW, were randomly divided into three groups. Three different diets were provided to each group: high FC ratio (35:65) with low-energy concentrate (HFC-LEC), high FC ratio with high-energy concentrate (HFC-HEC), and low FC ratio (25:75) with high-energy concentrate (LFC-HEC). After 10 d of feeding the diets, the CH4 concentrations for all steers were measured and analyzed in duplicate according to the protocol established in experiment 1. In experiment 1, the mean correlation coefficient between the CH4 concentration from respiration and eructation was highest when a combination of two normal distributions was assumed (r = 0.79). The most appropriate measurement times were as follows: 2 h and 1 h before, and 1 h and 2 h after morning feeding. Compared with LFC-HEC, HFC-LEC showed 49% and 57% higher CH4 concentrations in exhaled gas from respiration and eructation (P < 0.01). In conclusion, the LMD method can be applied to evaluate differences in CH4 emissions in cattle using the protocol established in this study. Lay Summary The hand-held laser methane detector (LMD) technique has been suggested as a potential method for measuring methane (CH4) emissions from enteric fermentation of ruminants in the field. This study aimed to establish a standard procedure for using LMD to assess CH4 production in cattle and evaluate the efficacy of the protocol to detect differences in CH4 emissions from cattle fed with diets of different forage-to-concentrate (FC) ratios which is known to affect CH4 emissions. Experiment 1 was conducted to establish a protocol for measuring and analyzing the CH4 emissions from cattle using LMD. In experiment 2, 30 Hanwoo growing steers were divided into three groups and fed with a diet of high FC ratio (35:65) with low-energy concentrate (HFC-LEC), high FC ratio (35:65) with high-energy concentrate (HFC-HEC), or low FC ratio (25:75) with high-energy concentrate (LFC-HEC). The CH4 concentrations for all steers were measured in duplicate according to the protocol established in experiment 1. HFC-LEC showed 49% and 57% higher CH4 concentrations in exhaled gas from respiration and eructation, respectively (P < 0.01), than LFC-HEC. In conclusion, the LMD method can be applied to evaluate differences in CH4 emissions in cattle using the protocol established in this study. The hand-held laser methane detector (LMD) technique has been suggested as a potential method for measuring methane (CH4) emissions from enteric fermentation of ruminants in the field. The LMD method can be applied to evaluate differences in CH4 emissions in cattle efficiently using the protocol established in this study.